On the legitimacy of coercion for the financing of public goods - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2009)
The literature on public goods has shown that efficient outcomes are impossible if participation constraints have to be respected. This paper addresses the question whether they should be imposed. It asks under what conditions efficiency considerations justify that individuals are forced to pay for public goods that they do not value. It is shown that participation constraints are desirable if public goods are provided by a malevolent Leviathan. By contrast, with a Pigouvian planner, efficiency can be achieved. Finally, the paper studies the delegation of public goods provision to a pro t-maximizing rm. This also makes participation constraints desirable.
Keywords: D02; D82; H41; L51; 330; Public goods; Mechanism Design; Incomplete Contracts; Regulation; Öffentliches Gut; Finanzierung; Mechanism; Unvollständiger Vertrag; Allokationseffizienz; Theorie